R3-D3: (Photo-)Realistic Real-time Representations of Dynamic 3D-Driven Industrial Trainings - Gunkel, Simon N. B.; Klunder, Tessa; Cernigliaro, Gianluca (Proceedings of the ACM International Conference on Interactive Media Experiences Workshops (IMXw); 2025: Proceedings of the ACM International Conference on Interactive Media Experiences Workshops, 2025)
Extended Reality (XR) technologies offer transformative potential to enhance remote communication in industrial settings, particularly by facilitating immersive and interactive experiences that bridge physical distances. In this paper, we outline some of the main challenges based on the shortage of experts and deficiencies of the quality of technical skills, of personnel. We also outline how Extended Reality can help with technical training and communication in the industry to mitigate these issues. We outline three different representation formats for (photo-)realistic real-time representations and give concrete examples on how these representation formats can be utilized in dynamic 3D-driven industrial XR applications to offer remote training, remote expertise and quality control, and general remote communication. Finally, the paper proposes a pipeline and generic tool that can significantly simplify testing and experimentation in different use cases of industrial training.